Three Generations of Experience and Thought in Microbiology and Infection - Morris Goldner (Canadian Journal of Infectious Diseases)
Views and comments were sought from Brian Lacey, who was professionally active from the 1930s to the 1970s, Alain Dublanchet, active from the 1960s to the 2000s, and Mark Pallen, active from the 1990s to 2000 and beyond. Professor Lacey was professor of microbiology at the Westminster Medical School, University of London, United Kingdom, for many years and is now retired. Docteur Dublanchet is the long time head of the laboratory of microbiology and virology at the Centre Hospitalier Intercommunal de Villeneuve-Saint-Georges in the greater Paris area. Professor Pallen is currently professor of bacterial genetics at the Medical School, University of Birmingham (United Kingdom); he is a keen enthusiast of genomic studies in the interest of molecular pathogenesis research. All three are medically qualified. Four questions were posed to each: